2015
DOI: 10.1002/cncr.29812
|View full text |Cite
|
Sign up to set email alerts
|

Role of race in oncogenic driver prevalence and outcomes in lung adenocarcinoma: Results from the Lung Cancer Mutation Consortium

Abstract: BACKGROUND The discovery of oncogenic drivers has ushered in a new era for lung cancer, but the role of these mutations in different racial/ethnic minorities is understudied. The Lung Cancer Mutation Consortium 1 (LCMC1) database was investigated to evaluate the frequency and impact of oncogenic drivers in lung adenocarcinomas in the racial/ethnic minority patient population. PATIENTS AND METHODS Patients with metastatic lung adenocarcinomas from 14 United States sites enrolled in the LCMC1. Tumor samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 29 publications
0
63
0
Order By: Relevance
“…Despite of improvements in clinical strategies, the 5-year survival rate after curative treatment is still very poor [1,2]. KRAS mutations were found to be significantly more frequent in adenocarcinoma patients [3].…”
mentioning
confidence: 99%
“…Despite of improvements in clinical strategies, the 5-year survival rate after curative treatment is still very poor [1,2]. KRAS mutations were found to be significantly more frequent in adenocarcinoma patients [3].…”
mentioning
confidence: 99%
“…Nevertheless, some of the observed differences may be representative of a difference in pathogenesis of cancer in AA as compared with CC patients. These differences could potentially help elucidate possible causes for increased mortality in AA patients, which currently remain unclear (18). Thus, additional research with larger cohorts should aid in further describing these differences.…”
Section: Discussionmentioning
confidence: 99%
“…possibly responsive to a targeted therapy (2024). Thus, it is important to ensure that all cancer patients, regardless of race, undergo genomic profiling in order to be treated with appropriate targeted therapies (18). …”
Section: Discussionmentioning
confidence: 99%
“…Steuer et al recently reported the results from the Lung Cancer Mutation Consortium (n=60 for African Americans and n=838 for Whites), which were similar to those of this study. They noted a lower frequency of oncogenic driver mutations in African Americans patients than in Whites after adjusting for smoking by a multivariate analysis, although the sample size of their study was also too small to obtain statistical significance (odds ratio 0.69; 95% confidence interval, 0.41-1.18; P=0.176) (18).…”
Section: Commentarymentioning
confidence: 91%
“…Subsequent studies showed that the frequency of EGFR mutations was high in Asians (50-60%) and low in Whites (10-20%), but their frequency in African Americans varied with reports (15)(16)(17). The nature and frequency of other oncogenic driver mutations in NSCLC among African Americans have been rarely reported (18,19).…”
mentioning
confidence: 99%